2016
DOI: 10.1111/nep.12556
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative biomarkers in renal transplantation

Abstract: This review summarizes the current evidence and potential clinical utility of established and novel renal biomarkers in predicting kidney transplant outcomes, including delayed graft function, acute rejection and graft loss. ABSTRACT:The emerging need for biomarkers in the management of renal transplantation is highlighted by the severity of related complications such as acute renal failure and ischaemia/reperfusion injury (IRI) and by the increasing efforts to identify novel markers of these events to predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 148 publications
(310 reference statements)
0
12
0
Order By: Relevance
“…Urinary interleukin‐18 (IL‐18) has also shown promising results . Evidence that other biomarkers of kidney damage, such as kidney injury molecule‐1 (KIM‐1) or liver‐type fatty‐acid‐binding protein (L‐FABP), is inconclusive. Further possible markers under assessment include the glycoprotein clusterin, the phosphoprotein osteopontin and the tumor necrosis factor α (TNF‐α) gene A20, markers of cell cycle arrest and inflammation, combinations of conventional and novel markers (e.g., creatinine, cystatin C, and malondialdehyde), T reg cell counts, and biomarkers obtained from hypothermic machine perfusion …”
Section: Prediction Of Dgfmentioning
confidence: 99%
“…Urinary interleukin‐18 (IL‐18) has also shown promising results . Evidence that other biomarkers of kidney damage, such as kidney injury molecule‐1 (KIM‐1) or liver‐type fatty‐acid‐binding protein (L‐FABP), is inconclusive. Further possible markers under assessment include the glycoprotein clusterin, the phosphoprotein osteopontin and the tumor necrosis factor α (TNF‐α) gene A20, markers of cell cycle arrest and inflammation, combinations of conventional and novel markers (e.g., creatinine, cystatin C, and malondialdehyde), T reg cell counts, and biomarkers obtained from hypothermic machine perfusion …”
Section: Prediction Of Dgfmentioning
confidence: 99%
“…When the damage was severe (BUO24), the urinary excretion of interleukin-18 (IL-18) have been validated as biomarkers for early prediction of acute kidney injury (AKI) and delayed graft function in transplantation medicine. 30 However, it has been reported that urinary NGAL , KIM-1 and IL-18 were not able to identify aetiology of AKI in kidney transplant recipients (KTR). 31,32 Because ureteral obstruction is one of the etiological causes of AKI in KTR, 33 further studies deserve to be performed to evaluate the presence of urinary Oatp1 in KTR and its potential role as an ureteral obstruction biomarker in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, conventional laboratory markers, such as serum creatinine, urine output in donors and cold ischemic time (CIT) are widely used to predict initial allograft function [ 9 ]. However, there are very limited reliable intraoperative methods to assess real-time allograft condition, resulting in late detection of slow allograft function and injury during the early post-transplant period [ 10 ]. Furthermore, transplant surgeons currently evaluate and predict initial allograft function in the critical early post-transplantation period through the assessment of color, texture, and capillary refill after reperfusion of the allograft, which is highly subjective and varies greatly based on the surgeons’ experience.…”
Section: Introductionmentioning
confidence: 99%